Analyzing Savings Behavior Among University Students: A Case Study of Bank's Financial Education Initiatives - Kok Ban Teoh; Saurabh Ravindra Nerkar; Sakshi Ajay Darware; Siti Nazurah binti Mohd Zaki; Nur Ain Afiqah Binti Mohd Taufik; Haziqzul Najmi Bin Abdullah; Zhang Renyue; Charu Padam; Daisy Mui Hung Kee (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2024)
This study investigates the impact of Maybank’s Financial Education Initiatives and financial goal-setting on the savings behavior of university students. Utilizing both primary and secondary data, the study aims to determine how financial education and the establishment of measurable financial goals influence students' savings habits. Primary data was collected through an online survey distributed to 200 university students using a Five-Point Likert Scale to measure responses regarding their participation in financial education programs, financial goals, and savings behavior. Secondary data was sourced from relevant academic journals focusing on accounting and finance research in the Asia Pacific region. The results reveal that both financial education and goal-setting significantly influence savings behavior, with financial goals exhibiting a stronger effect. Regression analysis shows that financial goals (? = 0.386) have a higher impact on savings than Maybank’s Financial Education Initiatives (? = 0.270). The study concludes that while financial literacy is crucial, goal-setting plays a more pivotal role in promoting consistent saving behavior. The findings imply that financial literacy programs should integrate goal-setting strategies to maximize their effectiveness in fostering long-term financial responsibility among students.